2010
DOI: 10.1159/000313923
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Breast Cancer to the Stomach Resembling Early Gastric Cancer

Abstract: Breast cancer metastases to the stomach are very rare. As characteristics of breast cancer metastases to the stomach, metastases of lobular carcinoma, mainly with signet ring cells, are frequently observed, and they are often difficult to distinguish from a primary gastric cancer with signet ring cells. Moreover, because no characteristic symptoms are shown and they involve a submucosal lesion, it is difficult to make a radiographic diagnosis. However, if a gastric lesion is observed after breast carcinoma sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…Incipient gastric lesions are most commonly referred to as primary gastric cancers. A case that was diagnosed as early gastric cancer discovered gastric metastasis of breast cancer using endoscopic biopsies (32), and another case revealed that definitive diagnosis of metastatic breast cancer was confirmed after endoscopic mucosal resection of a presumed primary early gastric carcinoma (33).…”
Section: Diagnosticmentioning
confidence: 99%
“…Incipient gastric lesions are most commonly referred to as primary gastric cancers. A case that was diagnosed as early gastric cancer discovered gastric metastasis of breast cancer using endoscopic biopsies (32), and another case revealed that definitive diagnosis of metastatic breast cancer was confirmed after endoscopic mucosal resection of a presumed primary early gastric carcinoma (33).…”
Section: Diagnosticmentioning
confidence: 99%
“…Some authors report an average time between primary tumor diagnoses and metastasis to the stomach ranging from 4 to 10 years 3,6, . The mean age of these metastatic tumors is predominantly in the perimenopausal period due to hormonal imbalances typical of this phase 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The CK7 monoclonal antibody is present in tumors with glandular pattern, being observed at a maximum rate of 90% of breast cancers. It suggests breast cancer metastasis considering that only 50-64% of adenocarcinomas of the stomach present this molecule 8 , 10 , 11 . On the other hand, CK20 antibody presence favors the diagnoses of primary cancers from stomach, large bowel and pancreas 7 , 10 , 13 , 15 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…[13] To be able to distinguish between gastric metastasis of breast cancer and primary gastric cancer, pathological and immunohistochemical analysis is recommended. [14] Histological features should be compared with those of primary breast cancer to confirm the diagnosis. GATA3 expression is most frequently observed in breast and urothelial carcinomas, and 91% of breast invasive ductal carcinomas exhibit GATA3 expression as evidenced by immunohistochemical analysis.…”
Section: Discussionmentioning
confidence: 99%